2014
DOI: 10.18632/oncotarget.2269
|View full text |Cite
|
Sign up to set email alerts
|

CD271 is a functional and targetable marker of tumor-initiating cells in head and neck squamous cell carcinoma

Abstract: Tumor-initiating cells (TICs) in squamous cell carcinoma of the head and neck (SCCHN) are best characterized by their surface expression of CD44. Although there is great interest in identifying strategies to target this population, no marker of these cells has been found to be functionally active. Here, we examined the expression of the purported marker of normal human oral epithelial stem cells, CD271. We show that CD271 expression is restricted to a subset of the CD44+ cells. Using xenograft assays, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 39 publications
3
60
0
8
Order By: Relevance
“…1B) (Zhou et al 2007;Clay et al 2010). Recently, additional potential CSC surface markers have been identified, including CD10 (Fukusumi et al 2014), CD98 (Martens-de Kemp et al 2013), CD271 (Murillo-Sauca et al 2014), CD166 (Yan et al 2013), and ABCG2 (Wan et al 2010;Table). A separate method of isolation and identification of CSCs has been through the increased ability of CSCs to efflux Hoechst 33342 dye (due to increased activity of CSC membrane transporters).…”
Section: Cell Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) (Zhou et al 2007;Clay et al 2010). Recently, additional potential CSC surface markers have been identified, including CD10 (Fukusumi et al 2014), CD98 (Martens-de Kemp et al 2013), CD271 (Murillo-Sauca et al 2014), CD166 (Yan et al 2013), and ABCG2 (Wan et al 2010;Table). A separate method of isolation and identification of CSCs has been through the increased ability of CSCs to efflux Hoechst 33342 dye (due to increased activity of CSC membrane transporters).…”
Section: Cell Markersmentioning
confidence: 99%
“…A study conjugating a bacterial toxin (cytolethal distending toxin) to an anti-human CD133 monoclonal antibody demonstrated inhibition of cell proliferation (Damek-Poprawa et al 2011), whereas another study using a single-chain variable fragment targeting CD133 showed marked reduction in tumor proliferation in cell and mouse models (Waldron et al 2011). Inhibition of CD271, as well, has been demonstrated in cell models to decrease tumor formation (Murillo-Sauca et al 2014). Overall, targeting CSC surface markers remains an intriguing option for treatment.…”
Section: Targeting Cell Surface Markersmentioning
confidence: 99%
“…The FACS analysis has assessed not only the mesenchymal origin but also the non-malignancy of our clone. In particular, the negative results obtained analyzing the main surface markers expressed within the majority of solid tumors (CD133, CD117, CD34 and CD271) (23)(24)(25)(26)(27), together with the cell inability to form colonies in soft agar (28), confirmed that no malignant transformation occurred during cloning of PDL cells. In order to assess its potential and capability to differentiate into different lineages, we induced the clonal CD44+ PDL line toward adipogenic and osteogenic phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…CD271 + MSCs demonstrated also higher cell proliferation capacity compared to the entire PA-MSC population [23]. However, CD271 has been also identified as a marker of tumor initiating cells that may affect cell survival and proliferation [24][25][26].…”
Section: Cd271 Mscs In Ivd Regenerationmentioning
confidence: 99%